2022
DOI: 10.1177/24730114221119758
|View full text |Cite
|
Sign up to set email alerts
|

The Statistical Fragility of Platelet-Rich Plasma as Treatment for Chronic Noninsertional Achilles Tendinopathy: A Systematic Review and Meta-analysis

Abstract: Background: Randomized controlled trial (RCT) outcomes reaching statistical significance, frequently determined by P <.05, are often used to guide decision making. Noted lack of reproducibility of some RCTs has brought special attention to the limitations of this approach. In this meta-analysis, we assessed the robustness of RCTs evaluating platelet-rich plasma (PRP) for the treatment of chronic noninsertional Achilles tendinopathy (AT) by using fragility indices. Methods: The present study was a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The values for FIs in this analysis are consistent with previous fragility analyses within different orthopedic surgery subspecialties, which reported median FIs ranging from 2 to 5 with associated FQs ranging from 0.032 to 0.111. [34][35][36][37][38][39][40][41] This suggests that the RCT data for dichotomous outcomes comparing CDA versus ACDF are at least comparably robust to data from trials from other orthopedic subspecialties. However, the continuous fragility metrics from the present study cannot be directly compared these values as the CFI and FI are inherently different in their derivation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The values for FIs in this analysis are consistent with previous fragility analyses within different orthopedic surgery subspecialties, which reported median FIs ranging from 2 to 5 with associated FQs ranging from 0.032 to 0.111. [34][35][36][37][38][39][40][41] This suggests that the RCT data for dichotomous outcomes comparing CDA versus ACDF are at least comparably robust to data from trials from other orthopedic subspecialties. However, the continuous fragility metrics from the present study cannot be directly compared these values as the CFI and FI are inherently different in their derivation.…”
Section: Discussionmentioning
confidence: 92%
“…Statistical Fragility of Continuous Outcomes in RCTs Evaluating CDA versus ACDF IQR: 1.9-13.3) for sports medicine and arthroscopy literature, Gupta et al 42 reported a median CFI of 6 (CFQ: 0.141) for 6 RCTs investigating intraoperative ketamine infusion during scoliosis surgery, and Xu et al34 reported a median CFI of 5 (CFQ: 0.154) for 8 RCTs evaluating platelet-rich plasma injection for Achilles tendinopathy. Ho43 …”
mentioning
confidence: 99%
“…Few studies have utilised this methodology in the orthopaedic literature due to its recent introduction [44,57]. Nonetheless, the median CFI of trials comparing surgical vs. non-surgical management of FAIS (CFI = 19) is higher than values reported in prior orthopaedic studies including Ortiz-Babilonia et al's study on trials assessing the management of degenerative cervical pathology (median CFI = 14, IQR: 9-22) [44], and Xu et al's study on trials assessing the use of platelet-rich plasma in the management of chronic non-insertional Achilles tendinopathy (median CFI = 5, IQR: 3.5-9) [57]. The trend of FAIS trials being less fragile than other orthopaedic trials is no longer present when studies assessing either minor or major variations in surgical techniques are included (median CFI = 4.8; range 1-32.2).…”
Section: Discussionmentioning
confidence: 99%
“…PRP is a source of growth factors and, consequently, has mitotic, angiogenic, and chemotactic properties, representing an adjuvant treatment alternative for acute and chronic wounds. Furthermore, the application of PRP has been shown to be effective not only in the repair of soft tissues [ 24 , 25 ], but also in bone and cartilage reconstruction, tendons [ 26 , 27 , 28 , 29 ], hair growth, etc. The addition of bioactive excipients, such as HA, appears to accelerate endothelial, epithelial, and epidermal regeneration of PRP [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%